Estrategias de marketing y su incidencia en el sindicato de choferes de la ciudad de Babahoyo en el año 2024. - Barrera Lozano, Bryan Alexander (2025)
This case study focuses on analyzing the marketing strategies of the Drivers' Union of the city of Babahoyo and its impact on customer acquisition, and reveals that the institution faces challenges when it comes to visibility and communication of its value proposition. The absence of an effective digital strategy has contributed to the acquisition of fewer clients compared to other institutions that have opted to take a more modern approach. The research makes use of qualitative and quantitative data through interviews with managers and customer surveys, it is evident that the institution has long made use of traditional media such as radio, print advertising and the classic word-of-mouth recommendation. Although they have tried to work with social networks, the impact generated is very little due to lack of content and consistency in publications, therefore, it is suggested that a combination of traditional media and digital marketing could be the key to notice an improvement in visibility and customer acquisition.